Perencanaan Pengendalian Polusi Udara pada Lingkungan Kerja KN. Collection - Yusuf Mauluddin; Ujang Cahyadi; Mirna Maria (Jurnal Kalibrasi, 2023)
KN. COLLECTION is a factory that produces skullcaps, located at Kp. By the way, Samarang Garut. In production which involves human labor and the workplace environment, there are dangerous factors that can harm workers' health. One of them is dust in the workplace environment. while in room area 2 (Manual Knitting Machine) it is 150 AQI. The dust content value in these two areas has exceeded the threshold value of 60 AQI. Data collection was carried out using quantitative data collection techniques, namely sampling 30 data, then testing the data for normality using SPSS with the Kolgomorv Smirnov method, the results showed that the data was normally distributed. Based on the control analysis that has been carried out using the FMEA method to find the cause of the air pollution that occurred in the production work room of KN. COLLECTION. In the risk assessment process using FMEA, the assessment components are divided into 3 components, namely Occurrence, Risk Impact and Risk Detection. The research carried out has the aim of obtaining results (output) in the form of proposed improvements that can be implemented by the company to minimize air pollution that occurs in the company. Namely, with the proposal to add an Exhaust Fan from the inside out to regulate the release of dust from inside the room out of the room, to help ensure indoor air circulation remains clean, healthy and fresh. As well as the proposed filter on the machine that emits dust, a drainage channel for the dust is also created, in order to minimize the dust produced by the automatic knitting machine at KN. COLLECTION and creating a clean and comfortable work environment for production.